ANALYSIS OF STUDENT ERRORS IN SOLVING STUDENT MATHEMATICS UAS QUESTIONS ACCORDING TO CASTOLAN CRITERIA - Idris, Mustamin; Lembang, Ulvina Tangke; Rizal, Muh.; Lefrida, Rita (JME (Journal of Mathematics Education), 2024)
This study aims to analyze the errors made by students in completing final semester exam (UAS) questions in the field of mathematics, namely linear programming, matrices and transformation geometry. The subjects of this study were students of class XI Nursing at SMK Kesehatan Indonesia Jaya Parigi. In determining the research subjects, purposive sampling technique was used . The data collection technique for this study used documentation of essay questions for the final semester exam and documentation of student answer sheets and interviews. The data analysis technique used according to Miles and Huberman is condensation of UAS and interview results data, presenting UAS and interview results data and drawing conclusions. The results of this study indicate that the errors made by students are conceptual errors, procedural errors and technical errors. Indicators of conceptual errors made by students are not being able to interpret problems/use terms, concepts, and principles, students are not able to choose formulas/properties correctly and students are not able to apply formulas/properties accurately. Indicators of procedural errors are inconsistencies in the solution steps with the questions asked and not being able to complete the questions until the final stage. Indicators of technical errors are errors in arithmetic operations and errors in moving numbers or arithmetic operations from one step to the next. Factors causing errors made by UAS participants are not understanding the questions well, lack of mastery of concepts in Matrix, Linear Programs and Transformation Geometry materials, rarely practicing reworking examples of questions, students only see and read examples of questions. Penelitian ini bertujuan untuk menganalisis kesalahan yang dilakukan oleh siswa dalam menyelesaikan soal ujian akhir semester (UAS) pada bidang studi matematika yaitu materi program linear, matriks dan geometri transformasi. Subjek penelitian ini adalah siswa kelas XI Keperawatan SMK Kesehatan Indonesia Jaya Parigi. Dalam penentuan Subjek penelitian dilakukan dengan teknik purposive sampling. Teknik pengumpulan data penelitian ini menggunakan dokumentasi soal uraian (essay) ujian akhir semester dan dokumentasi lembar jawaban siswa serta wawancara. Teknik analisis data yang digunakan menurut Miles dan Huberman yaitu kondensasi data hasil UAS dan hasil wawancara, menyajikan data hasil UAS dan wawancara dan penarikan kesimpulan. Dari hasil analisis lembar jawaban siswa pada materi program linear persentase jawaban salah 52%, persentase jawaban slah pada materi matriks 76% dan persentase jawaban salah pada materi geometri transformasi 50%. Hasil penelitian ini menunjukkan kesalahan yang dilakukan oleh siswa yaitu kesalahan konsep, kesalahan prosedur dan kesalahan teknik. Indikator kesalahan konsep yang dilakukan siswa tidak dapat menginterpretasikan masalah/menggunakan istilah, konsep, dan prinsip, siswa tidak dapat memilih rumus/sifat dengan tepat dan siswa tidak dapat menerapkan rumus/sifat secara akurat. Indikator kesalahan prosedur adalah ketidaksesuaian langkah penyelesaian dengan soal yang ditanyakan dan tidak dapat menyelesaikan soal sampai tahap akhir. Indikator kesalahan teknik adalah kesalahan pada operasi hitung dan kesalahan dalam memindahkan angka atau operasi hitung dari satu langkah ke langkah berikutnya. Faktor penyebab kesalahan yang dilakukan peserta UAS adalah tidak memahami soal dengan baik, penguasaan konsep pada materi Matriks, Program Linear dan Geometri Transformasi yang masih kurang, jarang berlatih mengerjakan kembali contoh-contoh soal siswa hanya melihat dan membaca contoh soal.Â